Ocular surface treatment in dry eye patients before corneal refractive surgery - O.A. Klokova; R.O. Damashauskas; M.S. Geidenrich (РМЖ "Клиническая офтальмология")
O.A. Klokova, R.O. Damashauskas, M.S. Geidenrich Krasnodar Branch of the S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Krasnodar, Russian Federation Aim: to analyze the prevalence of dry eye disease (DED) among adult patients with ametropias and the efficacy of its complex treatment when preparing the ocular surface for corneal refractive surgery. Patients and Methods: 1,762 patients with ametropias were examined. In addition to all of the standard eye checks, vital conjunctival and corneal staining, Scheimpflug corneal topography, and anterior segment OCT as well as patient survey were performed. Standard preservative-free tear substitutes with or without a short course of steroids, lubricants, 0.05% anionic cyclosporine emulsion (twice daily), and long-term punctal plugs were prescribed for DED. Results: mild DED was diagnosed in 1,021 patients (57.9%). Of them, corneal lesion was reported in 362 patients (35.4%) and asymptomatic DED in 250 patients (25.5%). Corneal topographic indices of one or both eyes were abnormal (as a result of DED) in 147 patients (14.4%). Significant (p≤0.05) increase in corneal epithelial thickness of one or both eyes was reported in 564 patients (55.2%). Ocular surface treatment in DED patients allowed for uncomplicated corneal refractive procedures while target refraction was achieved in 1,006 patients (98.5%). Conclusion: a complex diagnostic approach to DED involving specific tests, patient survey, corneal topography, and OCT provides the diagnosis of both manifest and latent DED. Combined treatment for conjunctival and corneal xerosis that includes tear substitutes, topical cyclosporine, and punctal plugs, improves ocular surface health in DED thus enlarging the list of indications and the safety of laser eye surgery in these patients. Keywords: dry eye disease, laser eye surgery, corneal refractive procedures, anionic cyclosporine emulsion, punctal plugs, corneal epithelium. For citation: Klokova O.A., Damashauskas R.O., Geidenrich M.S. Ocular surface treatment in dry eye patients before corneal refractive surgery. Russian Journal of Clinical Ophthalmology. 2020;20(4):180–186. DOI: 10.32364/2311-7729-2020-20-4-180-186.